Isolasi, Identifikasi, dan Produksi Miselia Rhizopus sp. Berkadar Asam Nukleat Rendah untuk Pengembangan Mikoprotein - Riza Firmansyah; Nampiah Sukarno; Utut Widyastuti Suharsono; Sukarno Sukarno; Wendi Nurul Fadillah (Jurnal Ilmu Pertanian Indonesia, 2024)
Fungi, including Rhizopus sp., are food sources that commonly contain high nucleic acid levels. Therefore, the nucleic acid content must be reduced to achieve health standard requirements. This study aimed to isolate, identify, and produce Rhizopus sp. mycelium containing low nucleic acid. The Rhizopus spp. were isolated from tempeh collected from 12 different areas in Indonesia. Fungal identification was conducted based on morphological characteristics. The fungal isolates were selected based on mycelial growth and spore production on PDA. Biomass production of mycelium was carried out in potato extract and soybean extract media obtained from 200 g/L and 333.3 g/L, respectively. In each medium, 6 sugar levels were added, namely 0, 2, 3, 4, 5, and 6 g/L. Mycelium nucleic acid content reduction was achieved by heat treatment at 50°C and 60°C for 15 minutes and measured by a spectrophotometer at 260 nm. Fifty-eight isolates that were identified into 3 species were obtained in this experiment: R. oryzae, R. stolonifera, and R. microsporus. R. Microsporus had higher mycelium biomass and lower spore number than the other species. R. Microsporus produced a higher mycelium biomass in the soybean extract medium with 5 g/L additional sugar. The nucleic acid content of the 50°C heat-treated mycelium was 1.82% and 1.73% at 65°C. These values fulfilled the standard of mycelial nucleic acid content permitted in food by the USDA. Keywords: morphology, Rhizopus microspores, spore, soybean extract, tempeh